Auctions for Transferable Objects: Theory and Evidence from the Vehicle Quota System in Singapore - LEE, David K. C. (Institutional Knowledge at Singapore Management University, 1993)
This paper studies the hypothesis that auctions with resale markets result in higher prices. The vehicle quota system introduced in Singapore in May 1990 provides the setting. The Certificates of Entitlement (COEs) necessary to purchase new cars were initially transferable for all quota categories. After October 1991, COEs for four major categories became non-transferable. Our results indicate that while the conversion to non-transferability eliminated speculation, it has also intensified competition among car distributors. Auctions for non-transferable COEs in fact led to higher COE prices in three of the four categories.